Physical exercise may improve problem-solving skills and emotional intelligence in patients with relapsing-remitting multiple sclerosis: A cross-sectional study - Tasci, Irem; Demir, Caner Feyzi; Bilek, Furkan; Albayrak, Sait (Elsevier Sci Ltd, 2022)
Background: Multiple sclerosis is a disease that can reduce the quality of life with a physical disability, neuropsychiatric disorders, and cognitive dysfunctions. Therefore, multiple sclerosis treatment should include treatments for cognitive and neuropsychiatric disorders and pharmacological treatments. This study aimed to examine the effects of exercise on neuropsychiatric disorders, problem-solving skills, and emotional intelligence in multiple sclerosis patients. Methods: Thirty-six female relapsing-remitting multiple sclerosis patients aged between 18 and 45 years, with an Expanded Disability Status Scale between 1 and 3, who were diagnosed with definitive multiple sclerosis according to the revised McDonald criteria were included in the study. Participants completed outcome measures before and after the 12-week exercise program. Demographic/clinical information of the participants was obtained at baseline, neurological examinations were performed, and graded exercise testing on a bicycle ergometer was performed to determine aerobic capacity. Short Form-12 Version 2, Hospital Anxiety and Depression Scale, Modified Fatigue Impact Scale, Problem-Solving Inventory, Emotional Intelligence Scale were evaluated before and after the exercise program of the participants. Results: While a significant increase was observed in the HRpeak values of the participants after the exercise (p < 0.05), the VO2max values also showed a highly significant difference compared to the pre-treatment values. (p < 0.01). While a significant difference was detected in the mental subparameter of Short Form-12 (p < 0.05), a high level of significant difference was found in the physical subparameter (p < 0.01). While no significant difference was observed in the Hospital Anxiety and Depression Scale anxiety subparameter (p > 0.05), a significant difference was found in the depression subparameter (p < 0.01). There was a significant difference in Modified Fatigue Impact Scale physical and cognitive subparameters compared to pre-treatment (p < 0.01). A significant difference was observed in the Emotional Intelligence Scale total score after the treatment (p < 0.01). Conclusions: The results of our study showed that exercise in relapsing-remitting multiple sclerosis patients provided significant improvements in emotional intelligence, improved neuropsychiatric parameters, and increased problem-solving skills. In addition, to the best of our knowledge, this study is the first study in the literature to investigate the effect of physical activity exercises on problem-solving skills in multiple sclerosis patients.
Keywords: Multiple sclerosis; Physical activity; Problem-solving; Emotional intelligence; Neuropsychiatric disorders